Analisis faktor-faktor yang mempengaruhi ekspor kopi Indonesia ke Jepang Periode 2000-2017 - Eko Purwanto; Erfit Erfit; Candra Mustika (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study aims to analyze the development of Indonesian coffee exports to Japan, Indonesian coffee production, world coffee prices, and the rupiah exchange rate against the dollar for the period 2000-2017, as well as to analyze the effect of Indonesian coffee production, world coffee prices and the rupiah exchange rate against the dollar on coffee exports. Indonesia to Japan for the period 2000-2017. This research uses descriptive and quantitative analytical methods. The descriptive analysis method is used to analyze the development of each research variable. The quantitative analysis method is used to analyze the influence of independent variables on variables. Based on the results of the study, it was found that the development of Indonesian coffee exports to Japan from 2000-2017 averaged -3.81%, the development of Indonesian coffee production in 2000-2017 averaged 0.99%, the development of world coffee prices 2000-2017 averaged 6.40% and the development of the rupiah exchange rate against the dollar for the period 2000-2017 2.54%. And during the 2000-2017 period, Indonesian coffee production and the exchange rate of the rupiah against the dollar had a significant effect on Indonesian coffee exports to Japan, while world coffee prices had no significant effect on Indonesian coffee exports to Japan. Keywords: Exports, Production, Prices, Exchange rates